Computer gesture control - Borovynska, Y.; Pinzari, M.; Chebotarova, I. (ХНУРЕ, 2022)
This article deals with the interaction of the high-level programming language Python in combination with an Arduino to create a video gesture control. The program was created with the required hardware and software. This gesture control is capable of performing various functions in the video properties, namely: video rewinding, playback and pause, volume change.
Keywords: Python; video